STUDI PENJAJARAN ARSITEKTUR CANDI BUDDHA DI SUMATERA DAN JAWA DALAM KONTEKS MAHAYANA VAJRAYANA DITINJAU DARI TATA MASSA, TATA RUANG, SOSOK, DAN ORNAMENTASI - Kukuh, Ravi; P. Herwindo, Rahadhian (Riset Arsitektur (RISA), 2024)
Abstract - Buddhist architecture in Sumatra and Java still needs to be studied further in relation to the study of relations because Buddhist architecture does not have books or buildings that serve as guidelines for Buddhist architecture in Indonesia. The Buddhist schools that have spread in Indonesia, namely Mahayana and Vajrayana, have long ago had roots in Hindu teachings which can be seen again from the spread of architecture that occurred in Indonesia. This research was conducted to determine the relationship between Buddhist temples in Sumatra and Buddhist temples in Java. Analysis regarding the similarities and differences between several temples in Sumatra and Java can produce influencing factors. Comparative qualitative research was conducted to find out the differences and similarities between Buddhist temples in Sumatra and Java by conducting a juxtaposition study, after which the analysis was given what factors were thought to influence the similarities and differences obtained. It was concluded that there are similarities and differences between the two architectures of Sumatran Buddhist temples and Ancient Mataram Buddhists, similarities are possible because Sumatran temples have a closeness or resemblance to the architectural style of Central Javanese temples which can be seen in the application of different temple architectural elements. adapted to the Sumatran temples. The difference also explains that there is a closeness of the architectural style that is implemented according to local wisdom or based on local genius which influences the differences. So based on the descriptive qualitative analysis, it is evident that there are similarities and differences in the juxtaposition study that connects the architectural elements of the temples that are the object of research. Keywords: candi architecture, Buddha, Sumatra, architectural elements